Effect of cavitation in cylindrical and two-dimensional nozzles on liquid jet formation - Muhammad Ilham Maulana; . Jalaluddin (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
Cavitation in various nozzles of different geometries and dimensions, i.e., two-dimensional (2D) and cylindrical nozzles, and liquid jets discharged from the nozzles are visualized using a digital camera, and the index for estimating cavitation in a nozzle is discussed. Simultaneous high-speed visualization of cavitation in the cylindrical nozzle and a liquid jet are also carried out to investigate the relation between cavitation and ligament formation. As a result, the following conclusions are obtained: (1) Flow pattern transition in cavitating flows induces the transition in liquid jet patterns. As the liquid flow rate increases, flow patterns of cavitating flows and liquid jets transit from (no cavitation and wavy jet), (developing cavitation and wavy jet), (supercavitation and spray), to (hydraulic flip and flipping jet); (2) When the trace of a cavitation cloud comes out of the nozzle, a ligament is formed at the liquid jet interface. (3) The collapse of cavitation clouds near the exit and induces ligament formation, which, in turn, causes liquid jet atomization; (4) The causal relationship between cavitation cloud and ligament formation holds not only in the two-dimensional nozzle but also in the cylindrical nozzle